Influence of soil-protective technologies on the characteristics of the soils of hop plants. (October 2019) - Smirnov, M; Smirnov, P; Alexeev, E; Maksimov, I; Kazakov, Y; Prokopeva, E
Abstract: It is known that one of the main and complex indicators of the soil is the density of its composition (volume mass). The widespread introduction of new technologies of tillage in our country only increases interest in the values of density in the new conditions. At the same time, soil hardness is also an important parameter characterizing agrophysical conditions of plant growth. We believe that research on the diagnosis of these soil parameters is not enough, so we have conducted research in this area. Traditional methods of tillage do not have a significant compacting effect in the surface layer. Most of the acquired parameters of the additional density are characterized by us as optimal. Only in some cases of ploughing the soil density decreased to 0.7…0.99 g / cm 3 . This indicates an excessively friable state. Processing of fields by "no-till" (zero) type leads to an increase of values of density of addition of the soil to 0.94…1.25 g / cm 3 . Hardness values also increased and reached 22.8 kgf / cm 2 (2.24 MPa). We see the reason for this phenomenon in the inevitability of the use of heavy-duty tractors. At the same time, the mass of the tractor itself almost levels the type of engine used – caterpillar or pneumatic wheels. Therefore, the objects of study were tractors of different classes, energy saturation, and weight. Soil samples were taken from arable and subsurface horizons from five conventional layers. The results showed that the impact of the drivers of the tractors increases the density of the composition of the soil in all conditional layers. However, the compact intensity on the layers differentiated depending on the weight of the tractor. The soil in the traces of tractors weighing up to 6-7 tons was compressed mainly in the Arab horizon (at a depth of 0.3 m), and in the subsurface (at a depth of 0.3-0.5 m) the compact was practically absent. Soil compaction by tractors weighing 8-11 tons occurred to a depth of 0.5 m. At the same time, the increase in volume mass in the layers of the arable horizon was from 0.25 to 0.35 g/cm 3 . The most effective way to restore the subsurface layer is the use of various subsurface agents in the autumn. Application in the winter of snow retention techniques allows one to accumulate in the loosened subsurface layer of additional moisture needed in the spring presowing period.